Epidemic spread of ST1-MRSA-IVa in a neonatal intensive care unit, Italy - Giuffrè Mario; Cipolla Domenico; Bonura Celestino; Geraci Daniela; Aleo Aurora; Di Noto Stefania; Nociforo Federica; Corsello Giovanni; Mammina Caterina (BMC, 2012)
Abstract Background Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has recently emerged as an important pathogen in neonatal intensive care units (NICUs). The purposes of this study were to characterize methicillin-resistant isolates from an outbreak in a NICU, to examine the genetic traits and clonality of CA-MRSA, and to review the characteristics and outcomes of the neonatal cases and investigate the routes of entry and transmission of the MRSA outbreak strain in the NICU under study. Methods The study NICU practiced an active surveillance program for multidrug-resistant organisms, including weekly cultures for detection of MRSA from nasal swabs among all the admitted neonates. All first isolates from surveillance cultures and all clinical isolates were submitted for susceptibility testing and genotyping. Data from each infant's medical records were prospectively included in a database, and the clinical features and outcomes of the colonized/infected infants were assessed. Results A total of 14 infants were colonized or infected by a strain of ST1-MRSA-IVa between April and August 2011. The CA-MRSA strain appeared to have been introduced to the NICU by an infected infant transferred from another hospital. The outbreak was successfully contained by multifaceted infection control interventions. Conclusions The results of this study confirm that NICU is a healthcare setting with a critical permeability to CA-MRSA. Active surveillance including molecular typing can help to detect and monitor the spread of antimicrobial drug-resistant organisms, and thus trigger timely control interventions.